Difficulties in English Speaking Faced by The Students of SMP Negeri 2 Kedu Temangggung in Academic Year 2008/ 2009 - Sri Suwarti, T; Andris Susanto, Dias (MAJALAH ILMIAH LONTAR, 2009)
Abstract: The aims of this study are to know the description of difficulties speaking in the classroom. The problem faced by students in the eighth grade, and how does the teacher solve the problems.The research method used in this study was descriptive qualitative study. Data were collected through interview and observation. The subject of this study was the eighth year students of SMP Negeri 2 Kedu Temanggung in Academic year 2008 / 2009. It is found that the teaching of English speaking applied in two main activities: It is found that there are several problems faced by students.The studentsâ problems are; Students felt Difficult in speaking because they got lack of vocabularies. The students didnât have spirit to practice their speaking ability. The lack of time in practicing the method instruction. The students got misunderstanding with speaking delivered by teacher. The students did not dare to use many kinds of vocabularies that have already given. Then there are some solutions; Training or asking them to try speaking English in their daily learning process. As a teacher in the class teacher should give more attention to the students such as; giving motivation, giving compliment, giving tips, advice, etc. In giving explanation, teacher should master in material fully, especially in speaking skill, and teacher should make the class sounds becoming English speaking area. Teacher should e able to manage the time allotment well in teaching speaking session. Speaking English lesson needs more practices orally rather than written one. To increase the dareness studentsâ speaking ability, they must be forced to speak little by little, words by words, then sentence by sentence. Finally, writers can conclude that; Teaching them using English not the whole in teaching and learning process, but teacher may use 50% in English and 50% in Bahasa. Teacher must be able to manage the time appropriately. S/he does not focus on the consuming materials but on the result of teaching process. To increase the studentsâ speaking ability, the student should try to speak in English more over with their friends surrounding. And they can apply what they have just got the materials from their teacher. Key words : difficulties, English speaking Abstract: The aims of this study are to know the description of difficulties speaking in the classroom. The problem faced by students in the eighth grade, and how does the teacher solve the problems.The research method used in this study was descriptive qualitative study. Data were collected through interview and observation. The subject of this study was the eighth year students of SMP Negeri 2 Kedu Temanggung in Academic year 2008 / 2009. It is found that the teaching of English speaking applied in two main activities: It is found that there are several problems faced by students.The studentsâ problems are; Students felt Difficult in speaking because they got lack of vocabularies. The students didnât have spirit to practice their speaking ability. The lack of time in practicing the method instruction. The students got misunderstanding with speaking delivered by teacher. The students did not dare to use many kinds of vocabularies that have already given. Then there are some solutions; Training or asking them to try speaking English in their daily learning process. As a teacher in the class teacher should give more attention to the students such as; giving motivation, giving compliment, giving tips, advice, etc. In giving explanation, teacher should master in material fully, especially in speaking skill, and teacher should make the class sounds becoming English speaking area. Teacher should e able to manage the time allotment well in teaching speaking session. Speaking English lesson needs more practices orally rather than written one. To increase the dareness studentsâ speaking ability, they must be forced to speak little by little, words by words, then sentence by sentence. Finally, writers can conclude that; Teaching them using English not the whole in teaching and learning process, but teacher may use 50% in English and 50% in Bahasa. Teacher must be able to manage the time appropriately. S/he does not focus on the consuming materials but on the result of teaching process. To increase the studentsâ speaking ability, the student should try to speak in English more over with their friends surrounding. And they can apply what they have just got the materials from their teacher. Â Key words : difficulties, English speaking